Coronary artery dimensions: Iranian population versus Indo-Asians and Caucasians. (October 2015) - Ghaffari, Samad; Mehdizadeh-Lame, Mohammad-Bagher; Sepehrvand, Nariman; Aslanabadi, Naser; Sohrabi, Bahram; Separham, Ahmad; Jamshidi, Peiman
Background: The dimensions of the coronary arteries have been shown to vary among ethnic groups. There are no data available regarding the normal size of coronary arteries in Iranians. This study aimed to investigate normal coronary artery dimensions in a Northwestern Iranian population and to compare it with pooled data of Indo-Asians and Caucasians in previous studies. Methods: The study included 200 adults with suspected coronary disease who were referred for elective coronary angiography between June 2012 and March 2013 and were found to have normal epicardial flow in the coronary arteries. Quantitative coronary angiography was carried out on the longest atheroma-free part of the proximal segment of each coronary artery in all patients. Two Indo-Asian and Caucasian groups were selected and pooled for comparison with the available reports on individuals without coronary artery disease. Results: The mean diameters of the left main coronary artery, proximal left anterior descending artery, proximal left circumflex, and proximal right coronary artery were 4.58 ± 0.80, 3.69 ± 0.64, 3.37 ± 0.73, and 3.47 ± 0.68 mm, respectively. The dimensions of the proximal part of the left main coronary artery and right coronary artery were significantly greater in the Northwestern Iranian population compared to the pooled Caucasian group. This difference was maintained even after correction for body surface area. Conclusion: Our data indicate larger coronary diameters in the Iranian population compared to Caucasians or South-Asians. Hence the high prevalence of coronary artery disease in Iran cannot be explained by coronary dimensions.